CAR-T Cell Therapy: Mechanism, Management, and Mitigation of Inflammatory Toxicities - Fischer, Joseph W.; Bhattarai, Nirjal (Frontiers in Immunology, 2021)
Engineered T cell therapies such as chimeric antigen receptor (CAR) expressing T cells (CAR-T cells) have great potential to treat many human diseases; however, inflammatory toxicities associated with these therapies present safety risks and can greatly limit its widespread use. This article briefly reviews our current understanding of mechanisms for inflammatory toxicities during CAR T-cell therapy, current strategies for management and mitigation of these risks and highlights key areas of knowledge gap for future research.